Asia and South America: A Quasi-Common Economy Approach - Canuto, Otaviano; Sharma, Manu (World Bank, Washington, DC, 2012)
The Asian style of regional integration may be seen as a 'quasi-common economy' that eschews a formal linkup in political or monetary terms, but manages to generate similar results by strong physical integration and distributed chains of production and service delivery. This note proposes the Asian quasi-common economy as a benchmark for South America's regional integration efforts because it is a better fit than the politically driven, broad-based, European style integrative process.